مهام المشرف التربوي حديث التوظيف بالمدارس الابتدائية من وجهة نظر معلمي المرحلة الابتدائية دراسة ميدانية بمدينة الاغواط - بلغيث خرفية خلود; كزواي عطالله (My University, 2023)
This study aimed to know "the tasks of the newly employed educational supervisor in the primary institutions in Laghouat, where the descriptive exploratory approach was applied in order to suit the nature of the study. Results to: - Accompanying students on their way outside the educational institution - Contributing to strengthening human relations and developing social and educational activities - To supervise students in the internal system - Receiving parents of students - Contribute to preparing for exams and competitions - Participation in the work of the beginning and end of the year - Directing the students during the meal - Maintaining and adjusting the order between classes and directing them towards the departments Keywords: educational supervisor